EXPERIENTIAL LEARNING DALAM MENSTIMULASI PERKEMBANGAN KOGNITIF ANAK USIA DINI PADA WAHANA KETAHANAN GEMPA BUMI - Filiza Kirena; Ahmad Samawi; Wuri Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early childhood disaster mitigation education requires contextual learning approaches that simultaneously stimulate cognitive development. One relevant approach is experiential learning, which enables children to construct knowledge through direct experience. This study aimed to describe the implementation of experiential learning in stimulating the cognitive development of children aged 5–6 years at the Earthquake Resilience Facility of KidZania Surabaya and to identify the supporting and inhibiting factors affecting its implementation. This study employed a qualitative approach with a case study design. The participants consisted of children aged 5–6 years, accompanying parents or teachers, and the facility's zupervisor. Data were collected through observation, interviews, and documentation and analyzed using the Miles, Huberman, and Saldana model. The findings revealed that role-play activities based on experiential learning provided meaningful learning experiences that stimulated children's learning and problem-solving abilities, logical thinking, and symbolic thinking. The implementation was supported by concrete learning media, a realistic simulation environment, interactive learning equipment, and active guidance from the zupervisor. Meanwhile, differences in children's characteristics, high visitor density, limited activity duration, and technical constraints became the main challenges. These findings indicate that experiential learning offers a contextual learning alternative for stimulating early childhood cognitive development while introducing earthquake disaster mitigation in meaningful and engaging ways